HUBUNGAN PENGUNGKAPAN INFORMASI GRAFIK KEY FINANCIAL VARIABLE DENGAN PERUBAHAN KINERJA DALAM LAPORAN TAHUNAN PERUSAHAAN YANG TERDAFTAR DI BEI - Andrenossa, Gleen; Sukartha, I Made (Buletin Studi Ekonomi; VOL.19.NO.2.AGUSTUS 2014.(PP 119-211), 2016)
The Relation of Financial Information Disclosure in Graph with Changes In Company’s Annual Reports Listed In Indonesian Stock Exchanges. Graph usage is positively related to the change of the company’s performance. Companies include graph information in company documents to make good performance more salient to the user, while companies do not include graph information to conceal poor performance. The use of graphs by management represents part of the impression management process, which concerns the manipulation of the content and presentational formats such as graphs or pictures. The preparers of graphs believe that they can design graphs to manage the viewer’s impressions. The result concluded that Indonesian companies tend to use key financial variable graph when the company’s performance has increased and that Indonesian companies that have decreasing trend tend to use favorable distortion that can favor the look of the company.   Keywords: company performance, key financial variable graph, impression management
Keywords: company performance, key financial variable graph, impression management